Políticas/poéticas de la memoria en la Castilla medieval: mediación clerical y materialidad del saber en los poemas del Ms. Esc. K-III-4 (Libro de Apolonio, Vida de Santa María Egipciaca, Libro de los tres reyes de Oriente) - Carina Zubillaga (Medievalista)
The Spanish clergy of the 13th century carried out a cultural policy of transmission of knowledge and preservation of memory through a poetics based on the exemplary nature of texts pouring their teaching through the mediation process identified with the translation of Latin sources to the vernacular languages, promoting their dissemination to a wider lay audience. Through the textual dynamics of territoriality and the physicality of the memory, clerical poems that integrate K-III-4 MS realize double spatial memory as a narrative device, through writing and codicological unit of compilation as privileged forms of a social and testimonial identity configuration.